PENGARUH TINGKAT PENDIDIKAN, KUALITAS PELATIHAN, DAN PENGALAMAN KERJA APARATUR DESA TERHADAP PEMAHAMAN LAPORAN KEUANGAN DESA (STUDI PADA KECAMATAN BANDA RAYA KOTA BANDA ACEH) - murina, sasha; Rahmawaty, Rahmawaty (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2017)
This study aims to determine the effect of Education Level, Quality Training, and Work Experience on the Understanding Village Financial Report.The data used in this study is the primary data by spreading the questionnaire to the village apparatus in Banda Raya District of Banda Aceh.The population in this study is the village apparatus that exists in Banda Raya District of Banda Aceh. The collecting of data and information needed in this research was done by field research. The data used is primary data collected directly from the subject of research by a questionnaire form. The testing of the influences of independent variables toward dependent variables was done by using multiple regressions model. The results of this research showed that both partially and simultaniously, The Level of Education, The Quality of Training, and Work Experience had an effect on The Understanding of The Village Financial Statements in the Banda Raya District of Banda Aceh